Designing New Material Based on Functionalized Multi-Walled Carbon Nanotubes and Cu(OH)2–Cu2O/Polypyrrole Catalyst for Ethanol Oxidation in Alkaline Medium - El Attar, Anas; Chemchoub, Sanaa; Diallo Kalan, Mamadou; Oularbi, Larbi; El Rhazi, Mama (Frontiers in Chemistry, 2022)
In this work, the deposition of copper (II) hydroxide (Cu(OH)2) and copper oxide (Cu2O) nanostructures on functionalized multi-walled carbon nanotubes - Polypyrrole are reported as an efficient electrocatalyst for ethanol oxidation in alkaline medium. In the first step, the deposition of functionalized multi-walled nanotubes of carbon (F-MWCNTs) on electrode surface was carried out using drop casting mode followed by the electrodeposition of Polypyrrole (PPY) and Copper nanoparticles (Cu-Nps) using galvanostatic mode. The Scanning electronic microscopy (SEM) and X-ray diffraction (XRD) were performed in order to study the morphology and the structure of the elaborated catalysts. The electrochemical characterization conducted by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) revealed that the introduction of functionalized multi-walled carbon nanotube enhances the electric properties of the nanocomposites and offers a large active surface area. The prepared electrocatalyst was then tested in a solution of 0.1 M NaOH containing 0.2 M of ethanol showing a high performance (7 mA cm-2 at 0.85 V vs Ag/AgCl) and good stability (over 1800 s) toward ethanol oxidation.